Global Software Development and Quality Management: A Systematic Review - Mishra, Deepti; Mishra, Alok; Colomo-Palacios, Ricardo; Casado-Lumbreras, Cristina (Lecture Notes in Computer Science, 2017)
This paper presents a systematic literature review of global software development (GSD) and quality management aspects. The main focus is to highlight the current research and practice direction in these areas. The results have been limited to peer-reviewed conference papers and journal articles, published between 2000 and 2011. The analysis reports that major studies have been performed in quality and process management, while verification and validation issues of GSD can only get limited attention among researchers. This indicates the need for future research (quantitative and qualitative) in these areas.
Keywords: global software development; quality; process; verification; validation; JCR; Scopus; WOS(2)